МИКРОБИОЛОГИЧЕСКИЕ ПРОЦЕССЫ ПРОТЕКАЮЩИЕ В ПОЧВЕ ПРИ ВНЕСЕНИИ ПОД ЛЮЦЕРНУ ОРГАНО-ХИМИЧЕСКИХ ВЕЩЕСТВ (Scientific journal of the Fergana State University, 2023)
Applied for succes of  lucernes 2 or 14 t/ h gazapai , 30 t/h azerbaijan and their various combinations positively influences the number of  bacteria increase (to 17,0-63,5),  mushrooms (to 0,5-4,4), actinomycetes (to 1,0-6,0)  improves the biological activity of the soil, consequences, its immunity to phytopathogens.